THE ADAPTATION OF MEN WHO DIVORCED - Isti Prihatiningsih; Retnaningsih Retnaningsih; Intaglia Harsanti (Jurnal Psikologi, 2006)
The aim of thi study is to know about the affect of divorce and the adaptation of men whodivorced and also his adaptation for this. This study is using case study with a 26 years oldman as a participant who already divorced since 2 years with 2 children. In the beginning ofthe divorce he felt emotion trauma, confused and anxiety about the way his children aregrown up. He tried to againts it and during the time he could adapt in the situation finally. Hegot the children and felt so happy because of that. He don’t bothered by his sexual needs andreplaced it by worked and exercised. Key words : adaptation, divorce